Improved Path Loss Models for Radiowave Propagation in Suburban Environment in The Universiti Putra Malaysia Campus and Taman Sri Serdang - Mansor, Ab. Razak (2005)
This thesis describes the development of a new path loss prediction model called Lp4 and an improved COST231-Walfisch-Ikegami (ICWI) model in suburban environment in Universiti Putra Malaysia campus and Taman Sri Serdang. The measurements were performed in line-of-sight propagation (for open terrain) and non-line-of propagation (for vicinity of building). The measurement system consists of a spectrum analyzer and a logperiodic antenna. The measured path losses have been compared with various propagation prediction models and results show that these entire models were not in good agreement with the measured path losses. The accuracies of the Lp4 and ICWI models were found to be within (3.00f 0.26)% of relative mean error for all measurement frequencies. A computer program FEPL integrating both models was developed using Agilent VEE . The FEPL program provides the utility for calculating the signal characteristics of radio propagation paths and is realized in the run time version. This program offers path loss results for both open terrain path loss (OTPL) and building environment path loss (BEPL).